When the earth stood still: air pollution during the Covid-19 quarantine – the case of São Paulo and Rio de Janeiro - Junkes, Janaína Accordi; Teixeira Cavalcante de Lima, Tainá; Francesca Carvalho Oliveira França, Giulia; Freitas Rodrigues, Diego (Sustainability in Debate, 2021)
In March 2020, the World Health Organization declared a global pandemic due to the new coronavirus (COVID-19). Several countries responded to this threat by introducing quarantine measures to reduce the transmission of COVID-19 in the community. These measures have drastically reduced human activities, causing an impact on urban air pollution due to the associated reduction in automobile use and other polluting activities. We investigated this effect with measurements of Particulate Material (PM10), Carbon Monoxide (CO), Nitrogen Dioxide (NO2) and Ozone (O3), carried out by the environmental departments of the cities of São Paulo and Rio de Janeiro, for two months in 2020. We compared them with data for the corresponding months in 2019, relating to the social isolation index, measured by the Mathematics and Statistic Institute of São Paulo (IME-USP). The results show a significant decrease in NO2 and CO and an increase in O3, and little change in Particulate Material.